HOW TO INCREASE GREEN PRODUCT PURCHASE INTENTION THROUGH GREEN BRAND POSITIONING, GREEN BRAND KNOWLEDGE, AND GREEN BRAND ATTITUDE - Aziz, Abdul; Kuswati, Rini (Program Pascasarjana STIE Amkop Makassar, 2022)
The purpose of this study was to analyse the effect of green brand positioning, green brand knowladge and green brand attitude on green product purchase intention This research method is quantitative. The population used in this study were FEB UMS students. The type of sampling used in this study is Non probability sampling with purposive sampling technique. The number of samples taken was 160 respondents. This type of research data is primary data. This research applies quantitative analysis methods using Partial Least Square (PLS) tools. The results of this study are that green brand positioning has a positive and significant effect on green product purchase intention, green brand knowladge has a positive and significant effect on green product purchase intention, and green brand attitude has a positive and significant effect on green product purchase intention.